Performance and emissions characteristics of ozonated coconut oil as a biofuel for diesel engines - Pham Khanh Truong (2009)
Increasing demand and tightening supply of fossil fuels for transport together with climate change concerns have spurred vigorous activity in the production and using of biofuels for internal combustion engines. Specifically, the use of biodiesel from esterified vegetable oils blended with diesel fuel has grown commercially in many countries. Alternative processes to esterification are also being pursued to produce biofuels in a possibly simpler and/or cheaper manner. This work examines a biofuel for diesel engines produced by an ozonation process composed of different stages, with and without catalysts, developed and promoted by Frontier Japan Inc., (FJI). Filtered crude coconut oil was utilized as feedstock for biofuel production using ozonation process were measured to determine their variation with the various stages of the entire oznation process. The resulting biofuel, ozonated coconut boil, was blended with neat diesel fuel at 1, 3, 5, 7.5, 10, and 20 percent by volume and tested on a chassis dynamometer using the Japanese 10-15 Mode driving cycle to determine performance and emmissions characteristics. Results of the measurements indicated that the first filtration stage yielded the most significant reduction in viscocity and cloud point, during the enire ozonation process. Flash point was significantly reduced after the first ozonation stage. These results suggested the importance of the first filtration stage in improving the selected biofuel properties thus warranting a more detailed study in the future. Chassis dynamometer test results showed that emissions of CO2, NO, NO2, NOx and THC for blends up to 10 % ozonated coconut oil were not considerably different from those of neat diesel fuel. The 20% blend gave 9.5% less CO2, 14.6% less NO, 10.5% less NOx, 19.5% less THC than neat diesel fuel. Application of a multi-objective optimization software, together with an arbitrary set of reduced emissions and best fuel economy objective functions showed that the 20% blend was the optimum among the ozonated coconut oil lends tested. It is recommended for future studies that vegetable oils withy more polyunsaturated components be used as feedstock.